Cellular phones as an m-commerce application in the emerging youth market in South Africa - Clarissa Muir; Andrea Crystal (Communicare)
The effects of wireless communication on society emphasise one of the discrepancies that exists between developed and developing countries like South Africa. Mobile commerce is experiencing a growth rate in the developed world unlike in South Africa. Wireless communication in the form of mobile communication is being adopted at a significant pace, especially among urban emerging youth markets in South Africa. This market’s connectivity is mainly via SMS. The most pertinent finding of the research is that the role of cellular phones as an m-commerce application in the emerging youth market is one of connectivity, lifestyle and usage convention.